In-vitro Evaluation on the Antimicrobial Potential of Allium sativum L. (Garlic) and Allium cepa L. (Onion) against Clinically Relevant Bacterial and Fungal Strains - Nivetha. S. (Research Perspectives of Microbiology and Biotechnology Vol. 8, 2024)
Synthetic drug adversities and emerging multi-drug-resistant microbial invasions pose a serious threat in unveiling natural counterparts of which phytochemicals are the best choice. Antimicrobial studies (disk-diffusion method) tested against Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Proteus mirabilis, Enterobacter species, Bacillus subtilis, Enterococcus species and Staphylococcus aureus, Candida albicans and Aspergillus niger using onion and garlic fresh extract, aqueous dilution as well as by combining both pure extracts (1:1) proves its potentiality with significant antimicrobial activity. Both extracts can serve as a powerful broad-spectrum antibiotic having comparable or even better activity to that of the control. Pure onion extract exhibits better activity against Enterococcus species (19.3mm against 17mm) whereas pure garlic extract (1:1) shows remarkable activity (18.3mm against 17mm) for Enterobacter species. Moreover, aqueous garlic extract shows a pronounced effect even against the selected gram-positive species also compared to its pure counterpart. Synergism records an appreciable activity against all the selected bacterial as well as fungal species comparable to that of the control itself proving its potentiality as a broad-spectrum antibiotic.